Comparison Between the Effects of Bupivacaine and Levobupivacaine for Spinal Anesthesia on QT Dispersion - Pehlivan, Veli F.; Akçay, Murat; İkeda, Özlem C. and Göğüş, Nermin (Cardiovascular & Haematological Disorders - Drug Targets, 2021)
Background: Bupivacaine and Levobupivacaine are frequently used local anesthetic drugs in spinal anesthesia practice. Both agents have arrhythmic effects on the heart. However, there is no clear information about which agent is more arrhythmogenic. Objective: The aim of this article is to investigate the effects of bupivacaine and its S (-)-enantiomer, levobupivacaine, on cardiac arrhythmias in patients. Methods: The study included 40 patients scheduled for inguinal hernia surgery. Patients were randomly divided into the following two groups using a sealed envelope method: Group I, the bupivacaine group (n = 20); and Group II, the levobupivacaine group (n = 20). The QT values were taken preoperatively and during the 10th of the spinal block, the 10th of the surgical incision, and the 10th postoperative minute. Additionally, systolic blood pressure (SBP), diastolic blood pressure (DBP), mean arterial pressure (MAP), oxygen saturation (SO2), and heart rate (HR) values, in addition to motor block (Bromage scale) levels and durations, were recorded for each patient. Results: HR values measured at 10 min after spinal block were significantly higher than the baseline values in the levobupivacaine group (p < 0.05). The corrected QT interval (QTc) values increased significantly at 10 minutes after spinal block and at 10 min postoperatively in the bupivacaine group (p < 0.05). QTd and QTcd measurements were taken at the 10th minute of spinal anesthesia, the 10th minute of the incision, and the 10th minute postoperatively. When compared to the levobupivacaine group, a statistically significant increase was found in the bupivacaine group (p < 0.05). Conclusion: Levobupivacaine allows greater hemodynamic stability, while bupivacaine affects QTc and QTd measurement times more. As such, we believe that levobupivacaine may be a better alternative to bupivacaine during clinical practice, particularly in patients with cardiac problems.
Keywords: arrhythmia